Nuclear myosin I regulates cell membrane tension - Venit, Tomáš; Kalendová, Alžběta; Petr, Martin; Dzijak, Rastislav; Pastorek, Lukáš; Rohožková, Jana; Malohlava, Jakub; Hozák, Pavel (Scientific reports, 2016)
Plasma membrane tension is an important feature that determines the cell shape and influences processes such as cell motility, spreading, endocytosis and exocytosis. Unconventional class 1 myosins are potent regulators of plasma membrane tension because they physically link the plasma membrane with adjacent cytoskeleton. We identified nuclear myosin 1 (NM1) - a putative nuclear isoform of myosin 1c (Myo1c) - as a new player in the field. Although having specific nuclear functions, NM1 localizes predominantly to the plasma membrane. Deletion of NM1 causes more than a 50% increase in the elasticity of the plasma membrane around the actin cytoskeleton as measured by atomic force microscopy. This higher elasticity of NM1 knock-out cells leads to 25% higher resistance to short-term hypotonic environment and rapid cell swelling. In contrast, overexpression of NM1 in wild type cells leads to an additional 30% reduction of their survival. We have shown that NM1 has a direct functional role in the cytoplasm as a dynamic linker between the cell membrane and the underlying cytoskeleton, regulating the degree of effective plasma membrane tension.
Keywords: exocytóza; Cells, Cultured; mikrofilamenta; lidé; Cell Membrane; Mice, Knockout; HeLa Cells; fibroblasty; Cell Nucleus; buněčné jádro; Actin Cytoskeleton; Myosin Type I; kultivované buňky; myši; Humans; Exocytosis; Mice; Skin; tvar buňky; Cell Shape; myosin typu I; Cell Movement; zvířata; buněčná membrána; kůže; pohyb buněk; HeLa buňky; Animals; myši knockoutované; Fibroblasts